Congenital syphilis: refining newborn evaluation and management in Shenzhen, southern China. Issue 4 (24th June 2010) - Wu, Da-Dong; Hong, Fu-Chang; Feng, Tie-Jian; Liu, Xiao-Li; Lin, Li-Jun; Tian, Li-Shan; Qiu, Li-Xia
Abstract : Introduction: Consistent definitions of congenital syphilis are critical for determining true incidences and setting up targets of elimination. This study aimed to assess the evaluation and management of infants at high risk of congenital syphilis with an antenatal syphilis-screening programme in the Shenzhen SEZ and to develop feasible definitions for the detection of congenital syphilis in China. Methods: A retrospective study was conducted of all standardised records of pregnant women with positive syphilis between 2003 and 2007. Infants at high risk of congenital syphilis were evaluated by laboratory tests at birth and longitudinal follow-up. A screening test-positive congenital syphilis case was defined based on a positive 19S-IgM-FTA-ABS result at birth. Assuming that 19S-IgM-FTA-ABS was the gold standard, the sensitivity and specificity of the ascertainment methods were calculated. Results: During the study period, 1010 live infants were born to women with active syphilis during pregnancy. 19S-IgM-FTA-ABS detected 42 screening-positive congenital syphilis cases and another nine cases were identified by longitudinal follow-up only. Using 19S-IgM-FTA-ABS as the gold standard, 'fourfold rapid plasma reagin (RPR) titres' had the highest sensitivity and specificity compared with the other two follow-up methods. Discussion: 19S-IgM-FTA-ABS makes congenital syphilis case classification simpler and faster for newborns. In areas where 19S-IgM-FTA-ABS is not available, comparing newborn RPR titres with maternal titres can be an alternative method. Meanwhile, positive follow-up results act as treatment indicators for older infants. As congenital syphilis definitions vary over the country, the Shenzhen programme suggested a practical model for surveillance and treatment in areas with or without available 19S-IgM-FTA-ABS testing.